2014
DOI: 10.1021/tx500100m
|View full text |Cite
|
Sign up to set email alerts
|

QSTR Modeling for Qualitative and Quantitative Toxicity Predictions of Diverse Chemical Pesticides in Honey Bee for Regulatory Purposes

Abstract: Pesticides are designed toxic chemicals for specific purposes and can harm nontarget species as well. The honey bee is considered a nontarget test species for toxicity evaluation of chemicals. Global QSTR (quantitative structure-toxicity relationship) models were established for qualitative and quantitative toxicity prediction of pesticides in honey bee (Apis mellifera) based on the experimental toxicity data of 237 structurally diverse pesticides. Structural diversity of the chemical pesticides and nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The model domain can be represented by ranges of the molecular descriptors for training set compounds [35]. In this study, a twodimensional descriptor space is considered.…”
Section: Applicability Domain Of the Sar Modelsmentioning
confidence: 99%
“…The model domain can be represented by ranges of the molecular descriptors for training set compounds [35]. In this study, a twodimensional descriptor space is considered.…”
Section: Applicability Domain Of the Sar Modelsmentioning
confidence: 99%
“…The unpredictability of chemical poisoning of bees may be due to an incomplete understanding of the complex underlying toxicology of pesticides. In addition, thoroughly evaluating the effects of a large number of chemicals on bee poisoning using experimental tests is still challenging because of cost, time, and ethical concerns [10,11]. Computational prediction of bee poisoning (CPBP) may help scientists to identify toxic chemicals faster [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These QSAR models for species of ecological importance are often developed using the well-characterised relationships between the physico-chemical properties of chemicals, their persistence and toxicity as well as their global environmental fate (Domine et al, 1992;Devillers and Flatin, 2000). QSAR models have already been applied to the prediction of ecotoxicological endpoints in species of ecological importance including trout, daphnia, quail and bees within the project DEMETRA (Benfenati et al, 2011) and more recently for qualitative and quantitative toxici ty prediction in bees using a global quantitative structure-toxicity relationship model (QSTR) (Singh et al, 2014). To address the needs for QSAR models predicting toxicity of PPPs in honey bees, we developed an in-house software using databases on acute contact data in honey bees from different sources and a k-Nearest Neighbor algorithm (k-NN).…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors identified numerous data gaps, such combined toxicity databases potentially allow developing predictive Quantitative Structure-Activity Relationships (QSAR) tools particularly because it is rather impossible to test all possible mixtures in bees for their acute or chronic effects. Such QSAR tools are only available for single chemicals but to date not for the prediction of combined toxicity (Venko et al, 2017;Singh et al, 2014;. Hence, this manuscript describes the development and application of three innovative predictive QSAR models for honey bees within the CORAL software namely (i) two regression-based QSAR models predicting acute (contact) mixtures potency (pLD 50-mix) in a quantitative manner, and (ii) a classification-based model predicting the nature of combined toxici ty for organic binary mixtures (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation